(untitled) (Biological Sciences - PJSIR, 2002)
The antimicrobial activity of the cold methanolic extracts of the leaf and root bark of Calotropis pr ocera (Ait) , (Fam: Asclepiadaceae) was determined using the agar diffusion method . Staphylococcus aureus, Escherichia coli, Candida albicans, Pseudomona s aeruginosa, Klebsiella aerogenes and Enterobact er aerogenes were used as test organisms. Antimicrobial activity was observed with the leaf extract on four of the organisms tested , while the root bark showed activity on only two of the test organisms. The minimum inhibitory concentration (MIC) for the positively tested organisms lie within the range of 10-50 mg mi-1. Phytochemical analysis conducted on the samples revealed the presence of saponins, glycosides, and simple sugars in the leaves, while the root bark was found to contain tannins in addition to these groups . Fractionation of the crude extract by solvent-solvent extraction procedure indicated that the organic acidic and organic basic fractions were more active. Infra-red (IR) spectroscopy of the two factions indicated the presence of carboxylic acids and carbonyl groups. The findings of this study conforms with the local use of the plant.